Superfluid density in metastable 3He-4He mixtures - Bodensohn, Joachim; Leiderer, Paul (My University, 1990)
We have studied superfluid 3He-4He mixtures quenched into nonequilibrium states inside the miscibility gap by means of second sound. From the results for the second sound velocity we conclude that the superfluid density in the metastable is well described by extrapolation from equilibrium values. The boundary of the metastable region, where nucleation processes set in rapidly, is reflected in a sharp increase of the second sound attenuation.
Keywords: 530